Challenges and Rationality in Choosing the Islamic Education Major in Islamic-Based Higher Education - Tressa Risdianti; Ahmad Jamin; Albertos Damni (STAI Terpadu Yogyakarta, 2024)
This research delves into the reasons behind the selection of the Islamic religious education major at Islamic-based universities, as well as the challenges faced when individual interests and chosen majors are not in alignment. The research employs a qualitative questionnaire as the primary data collection method. The objective of this study is to provide in-depth insights into the choice of the Islamic religious education major in the context of Islamic-based higher education institutions and how the challenges faced by students can be overcome to achieve more meaningful education and a more satisfying career in the future. The research findings indicate that not all students choose their majors in line with their interests. Several challenges arise when individuals encounter a gap between their interests and the reality in the academic environment. This research identifies potential solutions to bridge this gap.Top of Form